2014
DOI: 10.1371/journal.pone.0115403
|View full text |Cite
|
Sign up to set email alerts
|

LDL-Migration Index (LDL-MI), an Indicator of Small Dense Low-Density Lipoprotein (sdLDL), Is Higher in Non-Alcoholic Steatohepatitis than in Non-Alcoholic Fatty Liver: A Multicenter Cross-Sectional Study

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is associated with increased risks of atherosclerotic diseases, including cardiovascular disease. However, the difference in risk between patients with non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH) has not yet been determined. Accumulating evidence has shown that high amounts of small dense low-density lipoprotein (sdLDL) are closely associated with atherosclerotic diseases. This study investigated differences in risk factors for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
0
36
1
Order By: Relevance
“…To date, however, no studies have investigated whether the severity of coronary artery lesions differs between patients with NAFL or NASH. We previously reported that the low-density lipoprotein (LDL)-migration index (MI), an indicator of serum small dense LDL (sdLDL) concentration, is higher in patients with NASH than in those with NAFL, which corresponds to the alterations in lipid metabolism involved, and this suggests that the risk of atherosclerotic diseases may be higher in patients with NASH than in those with NAFL [13,14]. Therefore, we hypothesized that there is a higher risk of coronary artery disease (CAD) in patients with NASH than in those with NAFL.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, no studies have investigated whether the severity of coronary artery lesions differs between patients with NAFL or NASH. We previously reported that the low-density lipoprotein (LDL)-migration index (MI), an indicator of serum small dense LDL (sdLDL) concentration, is higher in patients with NASH than in those with NAFL, which corresponds to the alterations in lipid metabolism involved, and this suggests that the risk of atherosclerotic diseases may be higher in patients with NASH than in those with NAFL [13,14]. Therefore, we hypothesized that there is a higher risk of coronary artery disease (CAD) in patients with NASH than in those with NAFL.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with simple steatosis, nonalcoholic steatohepatitis (NASH) patients have increased levels of sdLDL that may, at least partly, explain the increased risk for atherosclerosis and cardiovascular diseases in these patients [16 & ]. In this context, LDL migration index, an indicator of sdLDL, was higher in patients with NASH compared with those with nonalcoholic fatty liver diseases [17].…”
Section: Predictive Role Of Small Dense Ldlmentioning
confidence: 84%
“…We conducted a PubMed search and three scientific papers were retrieved from the database as of the end of March 2020. All of these studies showed that LDL-c was associated with NAFLD [24,31,32] . Sun D-Q, Wu S-J,Liu W-Y, et al found that LDL-c was associated with NAFLD in the non-obese Chinese population in a cross-sectional and longitudinal study [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis reports that it is the relatively high prevalence of NAFLD found in the Asian population (27%) [9][10][11] . The prevalence rate of NAFLD in the general population of China varies from 24.77-43.91% in recent years [11,12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation